Etiological evaluation of stridor in children - Supriya, N; Murthy, G R Rajashekara; Kumar, P Prem; K S, Sanjay (Indian Journal of Child Health, 2020)
Background: Stridor is a harsh, vibratory sound produced when airway becomes partially obstructed, resulting in turbulent flow of air through large airways. Objectives: The objectives of the study were to find out the most common causes of stridor, according to the age group for the better management and outcome. Materials and Methods: The present study was a hospital-based observational study where in children between the age group of 0 and 5 years with stridor were studied over 1-year period at a tertiary hospital of south India from January 2017 to 2018. A total of 71 cases were included in the study. Children were subjected to chest X-ray, computed tomography scan, blood tests, laryngoscopy, and bronchoscopy according to requirement and findings complied and analyzed statistically. Results: Majority of the stridor cases were in the age group of